Al-Qur’an dan Nalar Ideologis: Integrasi Dakwah Aliran dalam Tafsir al-Furqan karya A. Hassan - Ghozali, Mahbub; Mursyid, Achmad Yafik (Universitas Islam Negeri Raden Mas Said Surakarta, 2021)
Using ideology in interpretation has become a major problem since the codification of interpretation. This kind of interpretation model emphasizes the meaning leads to a certain ideology to expand the range of understanding through publications. This was done by Hassan in his work, Tafsir al-Furqan, who made it as a medium of da'wah to spread Persis's belief about Islam. This study aims to find the ideological narrative in Hassan's interpretation. This study uses a qualitative method with content analysis as a data analysis tool to achieve this goal. This study finds that Hassan's efforts to provide a normative understanding of Islam with purification efforts start from positioning the Qur'an as the main guide that eliminates all existence of previous traditions. With this argument, all forms of tradition preservation and knowledge development cannot be the basis for forming a new religious practice that is not found in the Qur'an. Muslims must fully adhere to the Qur'an as the basis of Persis ideology.